Femoral Tunnel Length in Anatomical Double-Bundle Anterior Cruciate Ligament Reconstruction Is Correlated with Body Size and Knee Morphology - Yahagi, Yoshiyuki; Iriuchishima, Takanori; Iwama, Genki; Suruga, Makoto; Morimoto, Yusuke; Nakanishi, Kazuyoshi (The Journal of Knee Surgery, 2023)
The purpose of this study was to reveal the correlation between anteromedial (AM) and posterolateral (PL) femoral tunnel lengths in anatomical double-bundle anterior cruciate ligament (ACL) reconstruction and body size and knee morphology. Thirty-four subjects undergoing anatomical double-bundle ACL reconstruction were included in this study. Preoperative body size (height, body weight, and body mass index) was measured. Using preoperative magnetic resonance imaging (MRI), quadriceps tendon thickness and the whole anterior–posterior length of the knee were measured. Using postoperative computed tomography (CT), axial and sagittal views of the femoral condyle were evaluated. The correlation between measured intraoperative AM and PL femoral tunnel lengths, and body size and knee morphology using preoperative MRI and postoperative CT parameters was statistically analyzed. Both AM and PL femoral tunnel lengths were significantly correlated with height, body weight, posterior condylar length, and Blumensaat's line length. These results suggest that the femoral ACL tunnel length created using a transportal technique can be estimated preoperatively by measuring the subject's body size and/or the knee morphology using MRI or CT. For clinical relevance, surgeons should be careful to create femoral tunnel of sufficient length when using a transportal technique, especially in knees of subjects with smaller body size and knee morphology. Level of evidence is III.
Keywords: anatomy; anatomical double-bundle ACL reconstruction; femoral tunnel length